Telephone Survey: Caregivers' and Learners' Perspectives on SMS for Education in Kenya - Myers, Christina; Jordan, Katy; Khagame, Phoebe; Mumbi, Albina; Njuguna, Lydia; Zhao, Annette (EdTech Hub, 2022)
This document presents the structure and questions used for a telephone survey which was undertaken with a sample of learners who use the M-Shule platform and their caregivers, in Kenya, during July and August 2022. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7310489 ZenodoArchiveConcept: 7310488 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7310489 10.53832/edtechhub.0133 2405685:NP52QFM8
Keywords: _r:AddedByZotZen

The effect of internet services on child education outcomes: evidence from poa! Internet in Kenya - Okyere, Charles Yaw (Journal of Development Effectiveness, 2022)
In 2016-2018 poa! Internet, a private internet service provider, distributed free internet services across schools in Nairobi, Kenya. Using inverse probability weighting (IPW) method, the study finds that the intervention significantly increases students’ internet use and training, receipt of information on educational content, and participation in information and communication technologies (ICTs) education programmes. However, the study does not find evidence that internet services increase school attendance. The results suggest that facilitating access to internet services in schools can significantly increase child computer and internet skills and training in developing countries, even if those investments have limited gains on school attendance.
Publisher: Routledge _eprint: https://doi.org/10.1080/19439342.2020.1829001 KerkoCite.ItemAlsoKnownAs: 10.1080/19439342.2020.1829001 2339240:TRFENWZN 2405685:3YSCZCH4
Keywords: Internet services; Kenya; education; gender; quasi-experimental design

The Promise of Inclusive Digital Learning in Kenya - Government of Kenya (2022)
KerkoCite.ItemAlsoKnownAs: 2339240:MD6TC9XP 2405685:RHPUQZC5

Kenya Digital Master Plan 2022-2032 - Republic of Kenya ICT Authority (2022)
KerkoCite.ItemAlsoKnownAs: 2339240:2JU3HTBP 2405685:Z4EGG6C5

Keep Kenya Learning (KKL): Training to Engage Caregivers in Digital Learning - Keep Kenya Learning (2022)
KerkoCite.ItemAlsoKnownAs: 2339240:B9P3SYV3 2405685:439ATWCE

Government-led edtech initiatives to improve learning outcomes in Kenya (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7004972 ZenodoArchiveConcept: 7004971 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7004972 2405685:QH86RGE6
Keywords: _r:AddedByZotZen

Improving Early Grade Education Across Kenya - RTI International (RTI, 2022)
Tusome focuses on four key interventions developed and proven to improve literacy outcomes in Kenya. Learn about the impact of this program.
KerkoCite.ItemAlsoKnownAs: 2405685:4Y4R9CS6 2486141:L2RCITFW

Drought situation in the Kenya ASAL areas now at crisis level - Kenya | ReliefWeb - ASAL Humanitarian Network (2022)
News and Press Release in English on Kenya about Agriculture, Climate Change and Environment, Drought and more; published on 5 Oct 2022 by ASAL Humanitarian Network
KerkoCite.ItemAlsoKnownAs: 2339240:3PE84E95 2405685:I2LURL58

Engaging parents and caregivers in EdTech is critical to foundational learning in Kenya - Nicolai, Susan; Khan, Amina; Mwachi, Joan; Otieno, Jennifer Cotter (EdTech Hub, 2022)
Kenya, sometimes called the ‘Silicon Savannah’ of Africa, is home to one of the most vibrant EdTech ecosystems in Africa (see Otieno & Taddesse, 2020). Building on government initiatives such as the flagship Digital Literacy Programme (DLP), the country’s Covid-19 education response (Ngware & Ochieng, 2020) included tremendous efforts to provide distance learning solutions. This week, the Kenya EdTech Summit 2022 is bringing together many of those who have been making this happen to discuss the role of evidence and collaboration to accelerate the pace of progress in Kenya.
KerkoCite.ItemAlsoKnownAs: 2339240:FP2F79YV 2405685:BLIUPRZV

Professional Development on Digital Literacy and Transformative Teaching in a Low‐Income Country: A Case Study of Rural Kenya - Kerkhoff, Shea N.; Makubuya, Timothy (Reading research quarterly, 2022)
In recent years, the government of Kenya has implemented programs with the hope of moving the country to middle‐income status. The government has implemented the Digital Literacy Programme, distributing tablets to schools across the country, and also a new curriculum, promoting innovative teaching that includes digital literacy, learner‐centered teaching, and relevance to students’ lives. Our purpose in this research was to explore culturally sustaining teaching methods in line with the Kenyan government’s push for innovative teaching and digital literacy attainment for all students. We used case study methods to describe Kenyan teachers’ perceptions of innovative teaching and digital literacy while participating in the Inquiry Initiative, a three‐day professional development series. Participants included preschool, primary, and secondary teachers from Trans Nzoia County. Data sources were pre‐ and post‐surveys, participant‐generated artifacts, and interviews. Our participants perceived the following needs: new literacies for learners, creativity for learners, collaboration and group work, and creativity to overcome technological challenges. Overall, participants embraced learner‐centered teaching theoretically but found that the lack of technological resources created barriers to teaching digital literacy in a learner‐centered fashion. We found that teachers reported mostly using technology for teaching preparation and record keeping rather than engaging students in digital literacy practices. To solve technological challenges, teachers described having students work in groups and using smartphones. Future research could share more creative solutions to technical challenges in low‐income countries.
Place: HOBOKEN Publisher: Wiley KerkoCite.ItemAlsoKnownAs: 10.1002/rrq.392 2339240:ZUF5QSBN 2405685:TCG8Z8AZ
Keywords: 1‐Early childhood; 2‐Childhood; 3‐Early adolescence; 4‐Adolescence; 6‐Adult; Case Studies; Collaboration; Collaborative Learning; Computer literacy; Constructivism; Creative ability; Creativity; Critical Pedagogy; Culturally Responsive Pedagogy; Digital Literacies; Digital literacy; Digital/media literacy; Education & Educational Research; Educational technology; Gloablization and Literacy; Group work in education; Information literacy; Instructional strategies; methods and materials; Kenya; Literacies; Literacy; Literacy programs; Policy; Postcolonialism; Professional Development; Psychology; Psychology; Educational; Qualitative Research; Social Constructivism; Social Sciences; Socio‐cultural; Students; Study and teaching; Survey Research; Teacher attitudes; Teacher education; Teacher education; professional development; Teachers; Teaching; Teaching methods; Team learning approach in education; Transformative

Adoption of education technologies for learning during COVID-19 pandemic: The experiences of marginalized and vulnerable learner populations in Kenya - Ochieng, Vollan Okoth; Waithanji Ngware, Moses (International Journal of Educational Reform, 2022)
The onset of COVID-19 made governments and other education actors prioritize distance learning, particularly through education technologies (EdTechs). Most sub-Saharan African countries adopted and adapted this approach. This paper examines the extent of EdTechs’ deployment in Kenya during the COVID-19 pandemic among marginalized and vulnerable populations. A cross-sectional study design was adopted for the study from which this paper drew its data, with both secondary and primary data utilized. The findings show that marginalized/vulnerable learner populations are still left out on EdTech supported learning. This article proposes salient recommendations that could help advance inclusive education discussion and related EdTechs’ discourse.
KerkoCite.ItemAlsoKnownAs: 10.1177/10567879221076081 2339240:2LCBFF56 2405685:IST3UVII

Parent and implementer attitudes on gender-equal caregiving in theory and practice: Perspectives on the impact of a community-led parenting empowerment program in rural Kenya and Zambia - Okelo, Kenneth; Onyango, Silas; Murdock, Dawn; Cordingley, Kaylie; Munsongo, Kelvin; Nyamor, George; Kitsao-Wekulo, Patricia (BMC Psychology, 2022)
Fathers are often perceived to be mainly responsible for the provision of the family's economic needs. However, past studies have demonstrated that fathers’ involvement in parenting has great significance for the child’s holistic growth and development. Few studies have investigated fathers’ roles in the nurturing care of young children, particularly responsive care and stimulation, in sub-Saharan Africa. The study reported here was carried out as part of a larger study that sought to evaluate the effectiveness of the Moments That Matter (MTM) program in improving the nurturing care of young children in rural communities in Zambia and Kenya. The MTM program uses a parenting empowerment approach to promote bonding and interactions between caregivers and their children within the home, focusing on responsive care, early learning, and security and safety so that children reach their full developmental potential. Trained volunteers facilitated monthly primary caregiver support and learning groups and ECD home visits. Fathers were encouraged to participate in the home visits and to attend some of the group meetings on specific topics. The study reported in this paper aimed to establish the impact of the parenting empowerment program in promoting more gender-equal attitudes and practices on parenting among fathers (who were not the primary caregivers).
KerkoCite.ItemAlsoKnownAs: 10.1186/s40359-022-00866-w 2339240:9YBRQDN6 2405685:4UHGV9DW
Keywords: And holistic development; Childcare; Early childhood development; Early learning; Fathers’ perceptions; Fathers’ practices; Fathers’ roles; Parenting; Responsive care; Stimulation

Public Statement on the Status of Payments to County Governments FY 2021-2022 - Republic of Kenya National Treasury and Planning (2022)
KerkoCite.ItemAlsoKnownAs: 2339240:3Y2CWUVK 2405685:KVMAL7TJ

Ministry of East African Community (EAC), ASALs And Regional Development - The Ministry of East African Community, Arid and Semi-Arid Lands, Republic of Kenya (2022)
KerkoCite.ItemAlsoKnownAs: 2339240:M4AGM9PZ 2405685:9WMVHV9U

Developing a Proof of Concept for a Regional Learning Hub for Eastern and Southern Africa Part 2: Insights from user research - Rahman, Asad; Groeneveld, Caspar (EdTech Hub, 2022)
In 2021 the UNICEF Eastern and Southern Africa Regional Office (ESARO), UNESCO, UNHCR, the Inter-agency Network for Education in Emergencies (INEE) and EdTech Hub began collaborating to develop a Regional Learning Hub (RLH). The aim of the RLH is to create a platform to provide teaching and learning content aligned to the curricula of different countries in the region that is appropriate to local contexts. The RLH is envisaged as a platform where digital learning content has been pre-aligned with national curricula to enable use by governments and education stakeholders to facilitate quick selection of content for educational use in their regions. This document is the second of five reports on the development of a proof of concept for the Hub. It provides a summary of user research undertaken for the project. We recommend beginning with the Final report and then moving to any of the remaining four reports, depending on your interest. Inception report User research Skills taxonomy Content curation An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5803107 10.53832/edtechhub.0076 2405685:CI5UZ5R4 2405685:HU5IFEK9
Keywords: _r:AddedByZotZen

Developing a Proof of Concept for a Regional Learning Hub for Eastern and Southern Africa Part 1: Inception Report - Groeneveld, Caspar; Michels, Guillaume; Kaye, Tom (EdTech Hub, 2022)
In 2021 the UNICEF Eastern and Southern Africa Regional Office (ESARO), UNESCO, UNHCR, the Inter-agency Network for Education in Emergencies (INEE) and EdTech Hub began collaborating to develop a Regional Learning Hub (RLH). The aim of the RLH is to create a platform to provide teaching and learning content aligned to the curricula of different countries in the region that is appropriate to local contexts. The RLH is envisaged as a platform where digital learning content has been pre-aligned with national curricula to enable use by governments and education stakeholders to facilitate quick selection of content for educational use in their regions. This document is the first of five reports on the development of a proof of concept for the Hub. It provides a background and overview of the project. We recommend beginning with the Final report and then moving to any of the remaining four reports, depending on your interest: Inception report User research Skills taxonomy Content curation An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5803111 10.53832/edtechhub.0075 2339240:XBN27377 2405685:674LJ8EY 2405685:EW94QPAA
Keywords: _r:AddedByZotZen

Designing for Scale: Understanding design principles and learning process for a personalised learning platform in Kenya - EdTech Hub (EdTech Hub, 2022)
ZenodoArchiveID: 5596448 ZenodoArchiveConcept: 5596447 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.0053 2405685:27K3U5W4

Guidance Note on Education Data Mapping in Sub-Saharan Africa: Moving from theory to practice - Selwaness, Irene; Adam, Taskeen; Lawson, Laté; Heady, Lucy (EdTech Hub, 2022)
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6339212 10.53832/edtechhub.0096 2339240:VJZWBP65 2405685:6JLQ7UC6 2405685:KQUDWCXC
Keywords: _r:AddedByZotZen

Kenya's pioneering eLearning programme - iMlango (iMlango, 2022)
iMlango aims to improve education outcomes in maths, literacy & life skills for 180,000 children in 245 schools by delivering access to digital education services & content.
KerkoCite.ItemAlsoKnownAs: 2339240:KPD8MKWN 2405685:NDXD68C9

Lessons from Kenya’s Education Reforms - World Bank (2022)
KerkoCite.ItemAlsoKnownAs: 2339240:58C9VTTY 2405685:5S455QEI

Can Education be Standardized? Evidence from Kenya - Gray-Lobe, Guthrie; Keats, Anthony; Kremer, Michael; Mbiti, Isaac; Ozier, Owen (Becker Friedman Institute for Economics at the University of Chicago, 2022)
We examine the impact of enrolling in schools that employ a highly-standardized approach to education, using random variation from a large nationwide scholarship program. Bridge International Academies not...
KerkoCite.ItemAlsoKnownAs: 2339240:RHPEGZVF 2405685:GD26M8HS

Alarm over teen pregnancies as Kenya ranked third worldwide | Nation - Maichuhie, Kamau (2022)
KerkoCite.ItemAlsoKnownAs: 2339240:885ESW6Z 2405685:AKH9DB7U

Exploring the Landscape for Digital Education: Observations from Kenya, Nigeria, and Senegal - USAID (2022)
KerkoCite.ItemAlsoKnownAs: 2339240:PE4ILVUW 2405685:HTZC89KZ

A spatial database of public primary day schools in western Kenya - Macharia, Peter M.; Moturi, Angela; Mumo, Eda; Snow, Robert W. (Harvard Dataverse, 2022)
Understanding the location of primary schools relative to population is important to contextualize the time, or distance, that students must travel...
KerkoCite.ItemAlsoKnownAs: 10.7910/DVN/5N8LW2 2405685:X535MUN5 4042040:3JHDAWZB 4042040:HDKP4PJ6
Keywords: Other

Technology Use for Teacher Professional Development in Low- and Middle-Income Countries: Recommendations for policy from a systematic review - D'Angelo, Sophia; Hennessy, Sara; Kreimeia, Adam; Koomar, Saalim; Cao, Lydia; McIntyre, Nora; Brugha, Meaghan; Zubairi, Asma (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.0080 2339240:PRMHXVPE 2405685:7S9CUP77 2405685:HHXQI3S4 2405685:VU5JQKWG 2534378:BXN59IRN
Keywords: Read; Teacher education and training; _r:AddedByZotZen

The Kenya Ministry of Education’s response to the COVID-19 pandemic: Case study - Gichuhi, Loise; Kallsta, Jane (UNESCO IIEP, 2022)
KerkoCite.ItemAlsoKnownAs: 2339240:2TPWS8LU 2405685:TMVCYFZ7

Technology Enabled Learning in Kenya: KWA Ground Insights on Building Resilient Distance Learning Ecosystems - Otieno, Jennifer; Ward, Rebecca (IREX, 2022)
KerkoCite.ItemAlsoKnownAs: 2339240:8Q2N66WW 2405685:NID4DURJ
Keywords: ⛔ No INSPIRE recid found

Developing a Proof of Concept for a Regional Learning Hub for Eastern and Southern Africa Part 3: Skills taxonomy - Groeneveld, Caspar (EdTech Hub, 2022)
In 2021 the UNICEF Eastern and Southern Africa Regional Office (ESARO), UNESCO, UNHCR, the Inter-agency Network for Education in Emergencies (INEE) and EdTech Hub began collaborating to develop a Regional Learning Hub (RLH). The aim of the RLH is to create a platform to provide teaching and learning content aligned to the curricula of different countries in the region that is appropriate to local contexts. The RLH is envisaged as a platform where digital learning content has been pre-aligned with national curricula to enable use by governments and education stakeholders to facilitate quick selection of content for educational use in their regions. This document is the third of five reports on the development of a proof of concept for the Hub and describes our observations during the creation of a skills taxonomy. We recommend beginning with the Final report and then moving to any of the remaining four reports, depending on your interest: Inception report User research Skills taxonomy Content curation An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5803101 10.53832/edtechhub.0077 2405685:VFV5SG9H
Keywords: _r:AddedByZotZen

Study on the Use of ICT in Education and Remote Learning During Crises and the Required Investment for Digital Transformation for African Countries. Country Profile Report Kenya - Association for the Development of Education in Africa (ADEA) (2022)
KerkoCite.ItemAlsoKnownAs: 2339240:685BP9WI 2405685:SPLJ84ZF

Developing a Proof of Concept for a Regional Learning Hub for Eastern and Southern Africa Part 5: Final report - Groeneveld, Caspar; Michels, Guillaume; Kaye, Tom (EdTech Hub, 2022)
In 2021, the UNICEF Eastern and Southern Africa Regional Office (ESARO), UNESCO, UNHCR, the Inter-agency Network for Education in Emergencies (INEE), and EdTech Hub began collaborating to develop a Regional Learning Hub (RLH). The aim of the RLH is to create a platform to provide teaching and learning content aligned to the curricula of different countries in the region that is appropriate to local contexts. The RLH is envisaged as a platform where digital learning content has been pre-aligned with national curricula to enable use by governments and education stakeholders to facilitate quick selection of content for educational use in their regions. This document is the fifth and final report on the development of a proof of concept for the Regional Learning Hub. We recommend beginning with this document and then moving to any of the remaining four reports, depending on your interest: Inception report; User research; Skills taxonomy; Content curation An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5795656 10.53832/edtechhub.0079 2405685:5XBMPDX6
Keywords: _r:AddedByZotZen

Session 5: How can I use EdTech to ensure that students are provided with quality educational content at the right level? - Mazari, Haani; Kaye, Tom (2022)
The Strategic Choices for Education Reform workshop held in Zimbabwe in November 2022 aimed to provide a forum for senior government officials to reflect and consider the strategic reform options for their countries. The objective was to convene officials in key positions in the ministries of education, higher education, finance, and planning to learn about important issues and approaches in education; exchange experiences and lessons; develop an understanding of what is necessary to reconstruct better and more resilient education systems; and to transform the large potential of young people, through human capital investments, into development and prosperity. EdTech Hub was invited to facilitate the day of the workshop focused on harnessing ICT for better teaching and learning. This presentation is one of several used in the workshop to promote learning, discussion, and problem solving among the participants. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7341509 ZenodoArchiveConcept: 7341508 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7341509 10.53832/edtechhub.0139 2405685:NUTI6KUS 2405685:PPRW2NTQ
Keywords: _r:AddedByZotZen

Developing a Proof of Concept for a Regional Learning Hub for Eastern and Southern Africa Part 4: Content curation - Groeneveld, Caspar (EdTech Hub, 2022)
In 2021 the UNICEF Eastern and Southern Africa Regional Office (ESARO), UNESCO, UNHCR, the Inter-agency Network for Education in Emergencies (INEE) and EdTech Hub began collaborating to develop a Regional Learning Hub (RLH). The aim of the RLH is to create a platform to provide teaching and learning content aligned to the curricula of different countries in the region that is appropriate to local contexts. The RLH is envisaged as a platform where digital learning content has been pre-aligned with national curricula to enable use by governments and education stakeholders to facilitate quick selection of content for educational use in their regions. This document is the fourth of five reports on the development of a proof of concept for the Hub and describes our observations during content curation. We recommend beginning with the Final report and then moving to any of the remaining four reports, depending on your interest: Inception report User research Skills taxonomy Content curation An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5803092 10.53832/edtechhub.0078 2405685:9VKXVKGI
Keywords: _r:AddedByZotZen

How to Design EdTech Programmes That Lead to Gender-Transformative Change - Samuels, Fiona; Leon-Himmelstine, Carmen; Marcus, Rachel; Myers, Christina (EdTech Hub, 2022)
This paper outlines how EdTech programming can adopt a gender-transformative approach to improve gender equity in access and learning outcomes. It explains what the term ‘gender-transformative change’ means, and why it is needed. Some key dimensions of gender-transformative approaches in the specific context of EdTech initiatives are outlined, looking at how different approaches can enhance access to education and learning opportunities and improve outcomes, and challenge discriminatory gender norms and stereotypes. Based on a desk review of grey and published materials, this paper then presents and discusses insights from the approaches taken by four EdTech programmes. Keywords: EdTech; gender-transformative; country case studies; education; girls’ education An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6475261 10.53832/edtechhub.0090 2405685:DSG9QF4F 2405685:GBQT3KMA
Keywords: _r:AddedByZotZen

Experiment Types for EdTech - Rahman, Asad; Carter, Alice; WambûiKuria, Catherine; Mbugua, Ciku; Simpson, Lea; Kably, Nathan (EdTech Hub, 2022)
An EdTech Hub sandbox fast-tracks promising EdTech interventions by providing funding, tools, and access to evidence. It provides a space for partners to test and grow ideas in conditions of uncertainty. Since 2020, EdTech Hub has worked with partners in eight countries to test and grow EdTech based on our sandbox methodology. When testing and growing EdTech, this tool provides a non-exhaustive list of ways to design and run experiments. Keywords: sandbox; lean startup; lean impact; experiments; validation; prototype An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7245945 ZenodoArchiveConcept: 7245944 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7245945 10.53832/edtechhub.0128 2405685:X8MUXS39
Keywords: _r:AddedByZotZen

Guidance on Community Mobilisation for Girls’ Education - AlSheikh Theeb, Thaer; McGinty, Sara; Obaid, Rasha (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6396237 10.53832/edtechhub.0086 2405685:CVS2WZC3 2405685:FVSQD8MB
Keywords: F: Helpdesk response; _r:AddedByZotZen

Session 4: How can I rapidly upskill my large teacher workforce? - Koomar, Saalim; Proctor, Jamie (2022)
The Strategic Choices for Education Reform workshop held in Zimbabwe in November 2022 aimed to provide a forum for senior government officials to reflect and consider the strategic reform options for their countries. The objective was to convene officials in key positions in the ministries of education, higher education, finance, and planning to learn about important issues and approaches in education; exchange experiences and lessons; develop an understanding of what is necessary to reconstruct better and more resilient education systems; and to transform the large potential of young people, through human capital investments, into development and prosperity. EdTech Hub was invited to facilitate the day of the workshop focused on harnessing ICT for better teaching and learning. This presentation is one of several used in the workshop to promote learning, discussion, and problem solving among the participants. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7341501 ZenodoArchiveConcept: 7341500 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7341501 10.53832/edtechhub.0138 2405685:E7C9MN3V
Keywords: _r:AddedByZotZen

Perceptions of autism spectrum disorder among the Swahili community on the Kenyan coast - Greer, J. M. H.; Sood, S. S. M.; Metcalfe, D. R. (Research in Developmental Disabilities, 2022)
Background In high-income and Western societies there is great understanding and awareness of autism spectrum disorder (ASD); however, for many low-middle income countries, research and knowledge is notably lacking. In Africa, there is a growing prevalence of ASD due to increased diagnosis, yet it is still a poorly understood condition. Aims Emerging literature has emphasised how cultural and societal beliefs underpin the level of understanding of ASD, and which typically results in lack of awareness and acceptance. As such it is important to investigate the cultural perceptions towards ASD within low-middle income communities of African culture, to further understand the challenges and barriers individuals with ASD face. The aim of the current study was to probe participants from the Swahili community, on the coast of Kenya, of their cultural views towards ASD. Method Semi-structured interviews were conducted with seven participants, and the data analysed using thematic analysis. Results Three key themes developed from the data; stigma, lack of awareness, and Government responsibility. Conclusion Cultural perceptions negatively impacted awareness and are exacerbated by lack of directive from the Government in providing appropriate diagnostic and educational support.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.ridd.2022.104370 2339240:XBS9JT73 2405685:ZQLKDMWM
Keywords: ASD; Government responsibility; Lack of awareness; Stigma; Swahili community

Perceptions of autism spectrum disorder among the Swahili community on the Kenyan coast - Greer, Jo; Sood, S. S. M.; Metcalfe, Dale (Research in Developmental Disabilities, 2022)
Background: In high-income and Western societies there is great understanding and awareness of autism spectrum disorder (ASD); however, for many low-middle income countries, research and knowledge is notably lacking. In Africa, there is a growing prevalence of ASD due to increased diagnosis, yet it is still a poorly understood condition. Aims: Emerging literature has emphasised how cultural and societal beliefs underpin the level of understanding of ASD, and which typically results in lack of awareness and acceptance. As such it is important to investigate the cultural perceptions towards ASD within low-middle income communities of African culture, to further understand the challenges and barriers individuals with ASD face. The aim of the current study was to probe participants from the Swahili community, on the coast of Kenya, of their cultural views towards ASD.Method: Semi-structured interviews were conducted with seven participants, and the data analysed using thematic analysis. Results: Three key themes developed from the data; stigma, lack of awareness, and Government responsibility. Conclusion: Cultural perceptions negatively impacted awareness and are exacerbated by lack of directive from the Government in providing appropriate diagnostic and educational support.
1 citations (Crossref) [2024-04-29] KerkoCite.ItemAlsoKnownAs: 10.1016/j.ridd.2022.104370 2339240:H936FS6S 2405685:ZI8AAL6P
Keywords: ASD; Government responsibility; Lack of awareness; Stigma; Swahili community; ⛔ No INSPIRE recid found

Learning Continuity in Response to Climate Emergencies: Preliminary insights on supporting learning continuity following the 2022 Pakistan floods - Mazari, Haani; Baloch, Imdad; Thinley, Sangay; Kaye, Tom; Perry, Freya (EdTech Hub, 2022)
This resource is based on preliminary insights from EdTech Hub’s emerging study of Learning continuity in response to climate emergencies following the 2022 Pakistan floods. The intention is to support stakeholders to identify feasible ways of using EdTech in response to Pakistan’s 2022 floods. The design adopted for this resource balances generating primary insights from flood-affected parents and teachers quickly and complementing these with insights from the existing evidence base on education in emergencies globally and nationally. EdTech Hub’s study of learning continuity in response to climate emergencies is ongoing. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7326483 ZenodoArchiveConcept: 7326482 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7326483 10.53832/edtechhub.0134 2339240:JZC2BLQQ 2405685:FKCF86HV 2405685:IHTU7JRT 2405685:UXWWBVVX
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Session 3: How can I develop an aligned and actionable EdTech strategy - Wyss, Natalie; Mbugua, Wanjiku; Kaye, Tom (2022)
The Strategic Choices for Education Reform workshop held in Zimbabwe in November 2022 aimed to provide a forum for senior government officials to reflect and consider the strategic reform options for their countries. The objective was to convene officials in key positions in the ministries of education, higher education, finance, and planning to learn about important issues and approaches in education; exchange experiences and lessons; develop an understanding of what is necessary to reconstruct better and more resilient education systems; and to transform the large potential of young people, through human capital investments, into development and prosperity. EdTech Hub was invited to facilitate the day of the workshop focused on harnessing ICT for better teaching and learning. This presentation is one of several used in the workshop to promote learning, discussion, and problem solving among the participants. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7341466 ZenodoArchiveConcept: 7341465 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7341466 10.53832/edtechhub.0137 2405685:VVT2BI9M
Keywords: _r:AddedByZotZen

How EdTech Can Be Used to Help Address the Global Learning Crisis: A Challenge to the Sector for an Evidence-Driven Future - Hollow, David; Jefferies, Kate (EdTech Hub, 2022)
KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.0115 2339240:3KZX9ARU 2405685:BBQE9QUM 2405685:UUDK52LQ 2405685:YB52PCMQ
Keywords: ⛔ No INSPIRE recid found

Combining school-catchment area models with geostatistical models for analysing school survey data from low-resource settings: Inferential benefits and limitations - Macharia, Peter M.; Ray, Nicolas; Gitonga, Caroline W.; Snow, Robert W.; Giorgi, Emanuele (Spatial Statistics, 2022)
School-based sampling has been used to inform targeted responses for malaria and neglected tropical diseases. Standard geostatistical methods for mapping disease prevalence use the school location to model spatial correlation, which is questionable since exposure to the disease is more likely to occur in the residential location. In this paper, we propose to overcome the limitations of standard geostatistical methods by introducing a modelling framework that accounts for the uncertainty in the location of the residence of the students. By using cost distance and cost allocation models to define spatial accessibility and in absence of any information on the travel mode of students to school, we consider three school catchment area models that assume walking only, walking and bicycling and, walking and motorized transport. We illustrate the use of this approach using two case studies of malaria in Kenya and compare it with the standard approach that uses the school locations to build geostatistical models. We argue that the proposed modelling framework presents several inferential benefits, such as the ability to combine data from multiple surveys some of which may also record the residence location, and to deal with ecological bias when estimating the effects of malaria risk factors. However, our results show that invalid assumptions on the modes of travel to school can worsen the predictive performance of geostatistical models. Future research in this area should focus on collecting information on the modes of transportation to school which can then be used to better parametrize the catchment area models.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.spasta.2022.100679 2405685:EQ9TER5R 4042040:8UF2BKAH
Keywords: Catchment area models; Disease mapping; Missing locations; Model-based geostatistics; Prevalence; School survey

EdTech That Reaches Marginalised Learners: Relevant Examples for the Indonesian Context - Rui, Yang (Tingting); Upadhyay, Arjun (EdTech Hub, 2022)
This curated list of resources presents a sample of education technology programmes that effectively reach marginalised learners, including children with SEND, girls, and children in frontier, outermost, and disadvantaged regions. This list provides short summaries of lessons in using EdTech such as radio, television, and mobile phones to reach marginalised learners, emphasising interventions and evidence relevant to the Indonesian context. Keywords: marginalised learners, Indonesia, radio, television, mobile phones, girls, no-tech options An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6924683 10.53832/edtechhub.0102 2339240:LDWT8LYC 2405685:JPXVGB3A 2405685:MNMTIMGA 2405685:Q9J54HFA
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

EdTech Horizon Scan: Rapid scan of online safety in education - Mazari, Haani; Kaye, Tom (EdTech Hub, 2022)
This EdTech Horizon Scan examines the issue of online safety in digital education — why it should be prioritised, how it is currently being approached, and its potential to become central to education design in low- and middle-income countries. Given that the internet has no borders, there is much to be done to address online safety in all parts of the world — high-income and low- and middle-income countries alike. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7336710 ZenodoArchiveConcept: 7336709 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7336710 10.53832/edtechhub.0136 2339240:4TCBX2GH 2405685:3QBCENK5 2405685:AWHK2L8L
Keywords: _r:AddedByZotZen

Delivering Remote Learning Using a Low-Tech Solution: Evidence from an RCT during the Covid-19 Pandemic - Islam, Asad; Wang, Liang Choon; Hassan, Hashibul (EdTech Hub, 2022)
During the prolonged school closure due to the Covid-19 pandemic, many children in rural Bangladesh were missing out on formal education. What is more these children had limited access to distance learning modalities such as the internet, television, and radio. To counteract this poor access, this study used the widely accessible modality of mobile phones to deliver a set of audio lessons to primary school students using Interactive Voice Response (IVR). These lessons were developed using the Interactive Radio Instruction (IRI) method. An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5721401 10.53832/edtechhub.0070 2339240:CHJR9D5G 2339240:RFJZSHMG 2405685:FE3VBQQW 2405685:NFXKD34I 2405685:PU8D6GXN 2405685:SY9TIAMH
Keywords: _r:AddedByZotZen

Should we paint all classroom roofs white to improve learning in Tanzania? - Proctor, Jamie (2022)
A growing literature base has developed from Global North contexts, showing a clear link between classroom temperature and student learning outcomes. However, very little evidence shows how this impact translates to low- and middle-income countries (LMICs), where average classroom temperatures are often high. The hypothesis for the research was that classroom temperatures in Tanzania are high and that a white-paint-cool-roof intervention would help mitigate these high temperatures. This study includes a literature review to understand the classroom policy in Tanzania, establish links between temperature and learning, and assess temperature retrofit options. Following this, the study presents the results of an experiment to trial a white-paint cool roof against a blue-paint roof and an unpainted control roof. Finally, data analysis predicts the intervention effects over an entire year and the subsequent impact on learning outcomes. The learning outcomes analysis includes a cost-effectiveness analysis using the Learning-Adjusted Years of Schooling (LAYS) metric. Empirical evidence of temperatures inside classrooms in Dar Es Salaam suggests that the temperature often exceeds 40℃. Literature searches indicate that this is the first time classroom air temperatures have been recorded and published for East Africa. The experiment involved using a low-cost retrofit intervention to reduce temperature – by painting the classroom roof blue or white over eight days. Results showed that the White Paint Intervention (WPI) reduced the temperature by around 3.7℃ over the course of the school day and up to a maximum of 5℃. The WPI was roughly twice as effective as the Blue Paint Intervention at reducing interior air temperatures. The WPI results were then modelled to estimate the classroom temperature reduction over a year, based on the assumed 3.5℃ reduction. Finally, using estimates from the existing literature, the learning impact of the intervention was calculated. The results suggest that using the WPI intervention can improve learning by 7.1%, which translates to an estimated 3.2 LAYS per classroom per year, at a cost-effectiveness of 5.3 LAYS per USD100. The paper shows that the impact of high temperatures in classrooms is likely undermining the funding currently channelled to improve learning outcomes in the region. Further, a WPI retrofit intervention is effective at reducing classroom temperatures in Tanzania. Due to climate-change-induced temperature increases, the intervention effectiveness is likely to increase over the coming decades. This paper was submitted as a dissertation in fulfilment of an MSc in Sustainability and Adaptation in the Built Environment at the Centre for Alternative Technology, Machynlleth, Powys (Wales)
ZenodoArchiveID: 7139243 ZenodoArchiveConcept: 7139242 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7139243 10.53832/edtechhub.0122 2405685:Z8B66R9X
Keywords: _r:AddedByZotZen

Engaging Girls with E-Learning: A curated list of good practices - AlSheikh Theeb, Thaer (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5604677 10.5281/zenodo.5761966 10.53832/edtechhub.0069 2405685:CPP3A2WM 2405685:DM8N3E8E 2405685:PXUQJZTH
Keywords: Helpdesk Response; _r:AddedByZotZen

Pakistan Digital Learning Landscape Analysis - Zubairi, Asma; Khalayleh, Abdullah; Baloch, Imdad; Mazari, Haani; Kaye, Tom; Groeneveld, Caspar (EdTech Hub, 2022)
The Covid-19 pandemic has resulted in a dramatic increase in the role educational technology (EdTech) plays in education delivery. As schools have closed worldwide, EdTech has played a critical role in keeping children learning. However, as the pandemic has persisted, the optimism around EdTech has plateaued. It has given way to fears that children who are using EdTech are not learning, and that the most marginalised children are falling further behind due to the emergence of a digital divide. On average, only 34% of households across Pakistan have digital access and only 14% have access to laptops or computers. The access challenge is further intensified by demographics including gender, locality, and socio-economic status. This divide must be addressed if EdTech is to support effective learning for all children across all contexts in Pakistan. If left unaddressed, EdTech interventions can exacerbate a digital divide that further compounds the disadvantage of marginalised groups. Across the world, UNICEF has supported governments globally to deploy EdTech tools in response to the Covid-19 pandemic. To support this endeavour in Pakistan, UNICEF Pakistan is building evidence on digital learning to support the EdTech ecosystem in Pakistan. Evidence in this landscape review will support stakeholders including the Ministry of Federal Education and Professional Training (MoFEPT) and UNICEF Pakistan to develop long-term strategies to fortify Pakistan’s EdTech ecosystem. The purpose of this landscape review is to identify the challenges, emerging trends, and opportunities for engagement within Pakistan’s EdTech ecosystem. To do this, the landscape analysis collected and analysed data (both primary and secondary, and quantitative and qualitative) relating to technology-facilitated learning in Pakistan. In this way, this landscape analysis can both inform MoFEPT and UNICEF’s strategies and provide a resource for stakeholder (e.g., federal, provincial, and regional government agencies, development partners, and the private sector) engagement in technology-facilitated learning in Pakistan. Keywords: marginalised learners; out-of-school children; EdTech tools; Pakistan; foundational skills; infrastructure; MoFEPT; UNICEF An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5774707 10.53832/edtechhub.0093 2339240:SCCGE8HG 2405685:HEXCEXFK 2405685:NBAIXDE4 2405685:XMGEKJ3V
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Cost-Effective EdTech Paper 2: Good practice - Mitchell, Joel; D'Rozario, Jonny (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7106003 ZenodoArchiveConcept: 7106002 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7106003 10.53832/edtechhub.0119 2405685:Y3SBIPF9 2405685:ZVX4DTXQ
Keywords: _r:AddedByZotZen

Developing a national EdTech strategy - Coflan, Caitlin; Wyss, Natalie; Thinley, Sangay; Roland, Mark (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7065183 ZenodoArchiveConcept: 7065182 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7065183 10.53832/edtechhub.0142 2339240:HPTMF4RJ 2405685:2437EGZU 2405685:UCMLR25N
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Mapping and Analysing Digital Learning Platforms in Latin America and the Caribbean - Myers, Christina; Wyss, Natalie; Villavicencio Peralta, Xuzel; Coflan, Caitlin (EdTech Hub, 2022)
This document was produced in response to a request from the UNICEF Latin America and Caribbean Regional Office (LACRO) submitted to the EdTech Hub Helpdesk in October 2021. The UNICEF team requested a curated list of digital learning platforms in the Latin America and Caribbean (LAC) region and an analysis of a shortlisted series of platforms intending to explore their potential for at-scale implementation and impact. This report does not aim to cover every leading and innovative digital learning platform in the LAC region. Rather, it presents a list of promising platforms and discusses their design and implementation to explore their relevance and potential for at-scale impact. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7023230 ZenodoArchiveConcept: 7023229 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7023230 10.5281/zenodo.7038003 10.53832/edtechhub.0111 2405685:E2R8AXSA 2405685:SMH62I7W 2405685:VINQBTJ5
Keywords: _r:AddedByZotZen

Mapeo y análisis de programas EdTech en América Latina y el Caribe - Myers, Christina; Wyss, Natalie; Villavicencio Peralta, Xuzel; Coflan, Caitlin (EdTech Hub, 2022)
Este documento se elaboró ​​en respuesta a una solicitud de la Oficina Regional de UNICEF para América Latina y el Caribe al Servicio de Asistencia de EdTech Hub en octubre de 2021. El equipo de UNICEF solicitó una lista seleccionada de programas de EdTech en la región de América Latina y el Caribe (ALC) y un análisis de un conjunto de programas preseleccionados con la intención de explorar su potencial para la implementación y el impacto a escala. Este informe no pretende cubrir todos los programas EdTech innovadores en la región de ALC. Más bien, presenta una lista de programas EdTech prometedores y analiza su diseño e implementación con el fin de explorar su relevancia y potencial para lograr un impacto a gran escala. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7306712 ZenodoArchiveConcept: 7306711 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7306712 10.53832/edtechhub.0132 2405685:ACLTCQV2 2405685:XIIQ4FSE
Keywords: _r:AddedByZotZen